PENGARUH STORE ATMOSPHERE KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS DI KAFE SALWA HOUSE SIROJUDIN SEMARANG) - Agung Meiyanto S; Bulan Prabawani (Universitas Diponegoro, 2017)
The research was motivated by the growth of business, especially in the field of culinary or food. The food service businesses were challenged to make a difference or characteristic so the consumers can distinguish. Therefore, businesses should prepare a strategy that can be pleasing and build the enthusiasm of consumers, so its become an experience in consuming products and services.The purpose of this study to determine the effect of store atmosphere, quality products, and services quality on purchasing decisions at Salwa House Sirojudin Tembalang Cafe. This type of research is explanatory research, data collection technique through the questionnaires, literature study and interviews. The sampling technique used purposive sampling technique. The sample in this study amounted to 100 respondents who were visit to Salwa House Sirojudin Tembalang Cafe.The results of this study indicate that the store atmosphere (X1), product quality (X2) and service quality (X3) each simultaneously influence purchasing decisions (Y). Based on the results of the regression, the variable that has the most dominant influence is service quality (X3). Suggestions in this study the Salwa House Cafe needs to consider the atmosphere instore or outstore is balanced, has a variant characteristic menu and attentive service provided with adequate facilities.